Cisplatin-based chemotherapy for testicular germ cell tumors: complication rates of peripheral versus central venous administration - Worst, Thomas; Sautter, Lisa; Weiß, Christel; Häcker, Axel; Heinzelbecker, Julia (Urologia internationalis, 2016)
Objective: Despite the low local toxicity of the used agents, Cisplatin-based chemotherapy (CBP) for patients with testicular germ cell tumors (TGCT) is mostly delivered via a central venous access (CVA). Since 2008, CBP is given peripherally in our hospital. Methods: Medical reports of TGCT patients who received CBP between September 1991 and August 2014 were evaluated. Complications regarding the way of administration (CVA vs. peripheral venous catheter [PVC]) were classified according to the Common Terminology Criteria of Adverse Events. The complication rates were compared using chi square test and propensity score matching. Results: During 288 cycles in 109 patients, 85 complications (29.5%) were observed with similar rates for overall (PVC 31.3%, CVA 29.9%; p = 0.820) and grade I complications (21.3%, 25.4%; p = 0.470). More grade II complications were observed in the PVC group (10.0 vs. 1.5%; p < 0.001). Grade III complications requiring invasive treatment were found only in the CVA group (3.0%; p = 0.120). Using propensity score matching, no differences in overall (p = 0.950), grade I (p = 0.540) and grades II/III (p = 0.590) complications were seen. Conclusion: The peripheral and central administration of CBP has similar overall complication rates. Despite more grade II complications, the peripheral administration of CBP is a safe alternative for TGCT patients. Additionally, no severe grade III complications occurred.